Mohacolora gen. n., a new genus of Ennominae (Lepidoptera, Geometridae) from South-East Asia, with description of a new species - Stüning, Dieter; László, Gyula M. (Zootaxa, 2015)
The present paper contains the description of the new ennomine genus Mohacolora (Geometridae, Ennominae) and its type species M. bezverkhovi sp. n. (Vietnam, Myanmar, Bhutan and Nepal). A detailed description of the external morphological and genital characters of Mohacolora is given and the new genus is compared to the related genera Doratoptera Hampson and Descoreba Butler. Six colour photos of adult moths and 5 genitalia figures are provided.